Tripés em roseiras: identificação, monitoramento e controle químico - Fernandes, Winnie Cezario (2015)
The growth in the production of ornamental plants is increasingly significant in Brazil and in the Northeast region, but the occurrence of pests is shown as a limiting factor. To minimize losses, adequate control measures should be employed. Accordingly, the correct identification of pests, population monitoring and studies on managements should be performed. The objective of this study was to identify thrips species in rose, characterize and quantify the damage loss caused by arthropod pests in the production of roses in Serra da Ibiapaba; to assess the fluctuation of thrips species in ten cultivars of rose, at different stages of flower development and monitoring systems, and; evaluate the efficiency of pesticides on Frankliniella spp. The experiments were conducted at the Company “Reijers Produção de Rosas”, São Benedito, Ceará State, “Lagoa Jussara” in planting roses in greenhouses. Three species of thrips have been identified: Frankliniella schultzei (Trybom, 1910), F. occidentalis (Pergande, 1895) and Caliothrips phaseoli (Pergande, 1825) (Thysanoptera: Thripidae) with the largest recorded infestations for F. occidentalis and F. schultzei in phenological phases of roses, especially in flowering. The injury caused by thrips in floral cut roses button affected the quality invalidating them for marketing. There was no difference between the sampling periods (morning and afternoon) and sampling (tray beat and direct view of the floral button) to the ten cultivars of roses, so the choice of the time and method must be reconciled with practicality and cost. The insecticides demonstrated ability to cause mortality of thrips in extreme conditions, within completely enclosed structures (flower buds).